Drug Reaction with Eosinophilia and Systemic Symptoms - Hung, Wei-Kai; Chung, Wen-Hung (The New England journal of medicine, 2022)
Drug Reaction with Eosinophilia and Systemic SymptomsA 30-year-old man presented with a morbilliform rash and fever after taking an antimicrobial agent. Facial edema, eosinophilia, and elevated liver-enzyme levels developed later.